Collaborative Supervision in the Implementation of Social Assistance in Sumedang Regency - Atirista Nainggolan (International Seminar on Social Work Update, 2023)
This research refers to the implementation of the distribution of social assistance for the poor in Sumedang Regency. The implementation of social assistance for the poor empirically experienced many problems, one of which was an error in the target household data. The implication is that many citizens should be entitled to receive social assistance but do not receive social assistance, on the other hand, citizens who can receive social assistance should not be entitled to receive social assistance. Based on these problems, collaborative monitoring is needed to ensure the policy runs as it should. This supervision is carried out to ascertain whether the target of social assistance is following the criteria that have been previously set or if there is an error or discrepancy in the targeting of the social assistance program. This study uses a qualitative approach with a descriptive analysis method. The data collection used is an in-depth interview, observation, and documentation study. Meanwhile, the technique of checking the validity of the data uses the credibility test, transferability test, dependability test, and confirmability test. The results showed that there has been no collaborative supervision effort on the implementation of social assistance policies intended for poor families in Sumedang Regency. The supervision process is carried out using a closed internal control model, where other parties including the community do not have access to carry out supervision. Based on this, it is necessary to reconstruct the supervision model for the implementation of social assistance that allows collaboration between stakeholders in the field of supervision to produce an integrated and synergistic monitoring system.